E many pluribus unum: A behavioural macro-economic agent based model - Michele Tettamanzi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2017)
In this paper we develop a Hybrid Macroeconomic ABM. The economy is populated with firms heterogeneous in term of financial fragility, measured via the Equity Ratio. Firms are maximizing profit by choosing capital, which can not be raised on the stock market. Therefore they have to rely on a loan charged by the External Finance Premium that is decreasing in the Equity Ratio; profits are retained as net worth. The economy is populated also with consumers, whom optimize their utility holding individual non-rational expectations; thus they are heterogeneous in their expectations. The expectations formation process is the Heuristic Switching Model: given a fixed set of heuristics, agents choose the one which has performed the best in the past; this model has been extrapolated and validated in several Learn to Forecast Experiments. Thanks to the Variant Representative Agent approach, there can be built bottom-up a macro-economic system which encapsulates the heterogeneity by considering relevant moments rather than the whole the distributions of the heterogeneous characteristics of the agents. The emergent macro-economic system will be described by an optimized IS, a Taylor Rule and a Phillips Curve; thus the model tries to bridge NK-DSGE with ABM. The proposed approach result in a macro-economic system with a reduced dimensionality, thus it is analytical tractable and it resumes macroeconomic thinking: the ABM is used to link periods and keep track of the individual distribution, while the macro-economic model is a frame that pictures the value of the fundamentals given the distributions. The model is put at work through a fiscal shock and it shows it capabilities in disentangling the transmission of a shock in its direct and indirect effect: the former are the ones directly caused by the shocked variable, the latter instead derive from the evolution of the distributions. Moreover the model is also able to distinguish the contributions to the shock of the Representative Agent Component opposed to the Heterogeneous Agent Component.
Keywords: E32; E44; E70; D84; D90; 330; Heterogeneity; Financial fragility; Bounded Rationality; Heterogeneous Expectations; Aggregation; Business cycles